KINERJA SISTEM PENYAPU TIPE GUTTER BROOMS PADA PROTOTIPE KENDARAAN PENYAPU JALAN - Aditya Bayu Pratama; Sugiyanto Sugiyanto; Radhian Krisnaputra; Benidiktus Tulung Prayoga; Yosephus Ardean Kurnianto Prayitno; Isworo Djati (Jurnal Rekayasa Mesin, 2023)
The performance of the gutter brooms sweeping system was studied by conducting an experimental sweeping test. The test is carried out by operating a sweeper system to sweep plastic, paper, and leaf waste. The test results show that at a broom rotation speed of 150,6 rpm, the sweeping of plastic obtained a 100% sweeping success rate with the three settings for the height of the broom, while the sweeping of leaf waste obtained a 100% sweeping success rate at the broom position Â± 0 mm touching the road surface and the sweeping of paper waste obtained a 100% sweeping success rate at the broom position Â± 15 mm pressing the road surface. The comprehensive system of the gutter brooms type of road sweeper vehicle prototype can show sweeping performance with a 100% success rate, although the success rate of the sweeping is uncertain for different sweeping situations.